MANAGEMENT OF SECONDARY ANGLE-CLOSURE GLAUCOMA IN ANTERIOR SEGMENT DYSGENESIS AND ANTERIOR MICROPHTHALMOS PATIENT - syifa rahmani; Maula Rifada (Majalah Oftalmologi Indonesia, 2023)
Introduction: The majority of cases of anterior segment dysgenesis (ASD) and anterior microphthalmia are known to be complicated by angle-closure glaucoma, which is also the primary cause of visual loss. Medical therapy of this secondary glaucoma is frequently ineffective, necessitating surgery. However, managing the surgery in an eye with a crowded anterior chamber is difficult. This study aimed to report the management of secondary angle-closure glaucoma in anterior segment dysgenesis and anterior micropthalmos patient. Case Report: :  A  39-year-old  woman  presented  to  Glaucoma  unit  with  chief complaint  of  pain  on  the  right  eye.  She  also  noted  blurred  vision,  redness,  and headache  approximately  seven  months  before  presentation.  The  patient  had  a history of glaucoma since 5 years old, but hadn’t regularly visit for a long time. The  visual  acuity  was  1/60  and  intraocular  pressure  (IOP)  was  45.  Anterior segment   evaluation   revealed   scleral   thinning   with   injection,   microcornea, sclerocornea,  hazy  peripheral  cornea,  iridocorneal  adhesion,  shallow  anterior chamber, iris transillumination defect and lens opacity. A-scan biometry showed normal axial length. She was diagnosed with secondary angle-closure glaucoma with anterior segment dysgenesis, anterior microphthalmia and presenile cataract of the right eye. The patient underwent combined phacotrabeculectomy, pars plana vitrectomy and intraocular lens implantation. Discussion: Surgical procedure is indicated if pharmacological therapy cannot control IOP and glaucoma progressivity, including trabeculectomy combined with cataract extraction. However, cataract extraction is more difficult in shallow anterior eye chamber because the working field is narrower and the distance between the cornea and lens is closer. Some strategies to prevent this include pars plana vitrectomy (VPP). Conclusion: Anterior  segment  dysgenesis,  though  rare,  cause  vision  loss  by glaucoma as complication. Treatment of secondary glaucoma aim to lowering IOP to halt its progression. Combined phacotrabeculectomy, pars plana vitrectomy and intraocular  lens  implantation  was  a  safe  procedure  in  this  crowded  anterior chamber eye.